Faktor-Faktor Yang Mempengaruhi Underpricing Pada Perusahaan Yang Melakukan Initial Public Offering (IPO) Tahun 2018 - 2022 - Namira Ufrida Rahmi; Try Handopo Halim; Stevani Pebryan Saragih; Irna Triannur Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the factors that affect underpricing in companies that do initial public offerings (IPO) in 2018-2022. The factors studied include current ratio (CR), return on assets (ROA), debt to equity ratio (DER), earnings per share (EPS), and company age. Research methods used was used quantitatively using secondary data from related articles and journals. partial test results showed that Current Ratio, debt to equity ratio and company age had no significant effect on underpricing, meanwhile ROA and EPS had a significant effect on underpricing. Simultaneously Current Ratio, Return On Assets, Debt to Equity Ratio, Earnings Per Share, and Age Companies have a significant effect on underpricing Keyword: IPO, Underpricing, Current Ratio, Return on Asset, Debt To Equity Ratio, Earning Per Share, Age Companies